STANDING ABOVE THE LEVIATHAN: IMPLIKASI DIFUSI NORMA PERDAGANGAN WTO KE DALAM KEBIJAKAN IMPOR PANGAN INDONESIA PADA TAHUN 2018-2022 - Reskyana Lukman; Indra Kusumawardhana (TheJournalish: Social and Government, 2023)
The power of international organizations over the policies of developing countries has become a significant discourse in the era of globalization. This study elucidates Indonesia's food import policy between 2018 and 2022, which implements import policies regardless of surplus or bumper harvests, due to the influence of agricultural trade norms introduced by the World Trade Organization (WTO). The research aims to depict the process of the WTO as an international organization capable of controlling Indonesia's food import policy from 2018 to 2022 through the analysis of the diffusion process of WTO agricultural trade norms embedded within the Agreement on Agriculture (AoA). The method utilized in this study is qualitative research, involving data collection through literature review and applying the theory of norm diffusion to understand the inference process from global norms to the national policies of developing countries. The results demonstrate that the WTO can control Indonesia's food import policy through its engagement in the norm diffusion stage as a norm diffuser, establishing itself as an organizational platform in the norm emergence stage and providing legitimacy to norms in the acceptance stage. Therefore, during the internalization of norms by Indonesia, the WTO is able to monitor and control the country's agricultural policies, resulting in consistent food import policies despite bumper harvests or surpluses.